The Relationship of Acute Respiratory Infectional Diseases (ARI) With Climate (Rainfall, Air Quality, And Lighting) In Indonesia: Literature Review (Environmental and Public Health Maritime Journal, 2025)
BACKGROUND: Acute Respiratory Infection Disease (ARI) is a leading cause of mortality among children and toddlers in underdeveloped nations. Acute respiratory infection (ARI) has the potential to be transmitted via various viral agents, including Rotavirus and Influenza virus, as well as bacterial pathogens such as Streptococcus pneumoniae and Staphylococcus aureus. The age cohorts that exhibit susceptibility to Acute Respiratory Infections (ARI) include infants aged 0-12 months and toddlers aged 12-59 months, who are particularly prone to pneumonia. AIM: The objective of this study is to perform a comprehensive literature review pertaining to the impact of rainfall, air quality, and lighting on the occurrence of Acute Respiratory Infections (ARI) in Indonesia. METHODS: This study employs a Scoping Review methodology by utilizing the Google Scholar database and Academia.edu platform. A total of 49 journals were initially identified and subsequently narrowed down to 11 journals with matching titles. These 11 journals were then further assessed for eligibility based on the predetermined criteria set by the author, resulting in the selection of 6 journals. RESULTS: Evaluation of the research literature shows that there is a clear correlation between high rainfall, humidity and lighting on the occurrence of Acute Respiratory Infections (ARI). CONCLUSION: The occurrence of intense precipitation has the potential to amplify the incidence of acute respiratory infections (ARI) due to the resultant cold, Insufficient illumination and damp conditions in the affected region, especially in Indonesia.